Sacred places, civic purposes : should government help faith-based charity? - Dionne, E. J., Jr; Chen, Ming Hsu (Brookings Institution Press, 2001)
Long before there was a welfare state, there were efforts by religious congregations to alleviate poverty. Those efforts have continued since the establishment of government programs to help the poor, and congregations have often worked with government agencies to provide food, clothing and care, to set up after-school activities, provide teen pregnancy counseling, and develop programs to prevent crime. Until now, much of this church-state cooperation has gone on with limited opposition or notice. But the Bush Administration's new proposal to broaden support for ""faith-based"" social programs